2019
DOI: 10.3390/su11061657
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Double-Level Influence of Guanxi on Construction Innovation in China: The Mediating Role of Interpersonal Knowledge Sharing and the Cross-Level Moderating Role of Inter-Organizational Relationships

Abstract: Guanxi, a Chinese term that defines social networks of power and benefits, can be divided into inter-personal and inter-organizational relationships. Guanxi significantly influences construction innovation in China. Many studies have examined the relationship between guanxi and construction innovation at the project or organizational level. However, few of these studies explain how guanxi might affect an individual’s innovative behaviour from a double-level perspective. This paper builds on social capital theo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 85 publications
(104 reference statements)
1
8
0
Order By: Relevance
“…Furthermore, the results highlight the role of trust as a contextual factor in the Chinese culture, where trustful relationship leads to strong ties (Tortoriello et al, 2012), so there will be less concerns for knowledge being misused (Krackhardt, 1999;McEvily, 2003, 2008). This finding captures the relationship aspect of knowledge transformation, and further contributes to the literature on mechanism of knowledge transformation, as trustful relationship facilitates shared values and understanding of interests among knowledge actors so they are able to engage in knowledge transform at pragmatic boundaries (Wang et al, 2012;Qian et al, 2019).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Furthermore, the results highlight the role of trust as a contextual factor in the Chinese culture, where trustful relationship leads to strong ties (Tortoriello et al, 2012), so there will be less concerns for knowledge being misused (Krackhardt, 1999;McEvily, 2003, 2008). This finding captures the relationship aspect of knowledge transformation, and further contributes to the literature on mechanism of knowledge transformation, as trustful relationship facilitates shared values and understanding of interests among knowledge actors so they are able to engage in knowledge transform at pragmatic boundaries (Wang et al, 2012;Qian et al, 2019).…”
Section: Discussionsupporting
confidence: 57%
“…Guanxi is viewed as interpersonal bonds that are cultivated through long-term relationship building to create certain expectations and duties in daily interactions, business activities and organizational behaviors (Wang et al , 2012). Existing literature about Chinese firms has found that in situations where there is a highly trustful relationship or there is perceived shared understanding of interests and common values, parties are more willing to engage in social exchange and cooperative interactions such as knowledge transfer (Wang et al , 2012; Qian et al , 2019).…”
Section: Factors Influencing Knowledge Transfer Across Boundariesmentioning
confidence: 99%
“…Innovation begins at the organisational level, shifts to the conscious creation of individual members, and affects job performance and behaviour changes. Therefore, innovative behaviour can be more freely expressed during stable work performance, based on intimate relationships (Qian et al 2019). Innovative behaviour is also a form of voluntary social action that is closely related to the sense of joy and accomplishment derived from reflecting actual changes in the workplace based on the members' progressive attitudes (Kuncoro and Suriani 2018;Sameer 2018).…”
Section: Innovative Behaviourmentioning
confidence: 99%
“…It is an employe behavior that is a key dynamic for the success of knowledge-intensive organizations ( Ding et al, 2017 ; Stenius et al, 2017 ; Mc Evoy et al, 2019 ; Al-Kurdi et al, 2020 ), such as healthcare organizations. Although the issue of KS has been widely discussed in the growing literature on the topic ( Han et al, 2019 ; Qian et al, 2019 ; Al-Kurdi et al, 2020 ; Jiang and Xu, 2020 ), the number of studies contributing to the interpretation of and solutions to developing KSB in healthcare organizations is still limited. Accordingly, determining how to encourage employes to willingly share knowledge and in turn improve performance and the quality of medical services is a key issue for healthcare organizations.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…However, even though the factors affecting KS have been extensively investigated, gaps remain in the existing research on knowledge sharing behavior (KSB). First, a significant amount of research has explored the factors affecting KSB based on the social exchange theory, which proposes that human behavior is driven by individual expectations of the costs and benefits inherent in interpersonal exchanges ( Yan et al, 2016 ; Wu and Lee, 2017 ; Curtis and Taylor, 2018 ; Qian et al, 2019 ). However, focusing on understanding individuals’ willingness to share knowledge for the purpose of the exchange of benefits may not be sufficient to explain proactive KSB ( Kang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%